STUDI POTENSI LIMBAH TEMBAKAU MENJADI BIO-OIL MENGGUNAKAN METODE FAST-PYROLYSIS SEBAGAI ENERGI TERBARUKAN - Rafiqi Rajauddin Amin; Rimbi Rodiyana Sova; Dewinta Intan Laily; Dina Kartika Maharani (Jurnal Kimia Riset, 2020)
The rapid development of industry causes the need for fuel and energy to increase, especially fossil fuels (petroleum). This has the effect of an energy crisis. Biomass is of particular concern as one of the renewable energy sources to address the current energy crisis.  Biomass consists of hemiselulose, cellulose, and lignin that can be converted into liquids (bio-oils) of pyrolysis. One of the wastes that can be converted into bio-oil is tobacco waste. Tobacco waste is produced by more than 2 million tons eachs. The waste has the potential to be further processed into bio oil using fast pyrolysis method with efficient and quality bio-oil manufacturing measures. The bio-oil results from tobacco waste using the fast pyrolysis method have values of carbon, hydrogen, nitrogen, oxygen and other organic compounds and the H/C ratio is greater than the yield of tobacco waste bio-oil using the low pyrolysis method. Where the bio-oil of tobacco waste using the fast pyrolysis method has a high heating value equivalent to the distribution of hydrocarbons from biodiesel, which means it has the potential as an alternative energy to replace petroleum. The potential as a substitute fuel for petroleum must also be balanced with fast and efficient production, maximizing bio-oil production by selecting the reactor and the optimum temperature usedKeywords: Waste, Tobacco, Bio-Oil, Renewable Energy, Fast-pyrolisis